Pemodelan dan Simulasi Kinetika Reaksi Alkoholisis Minyak Jarak Pagar (Jatropha Curcas) dengan Katalisator Zirkonia Tersulfatasi - Heri Rustamaji; Hary Sulistyo; Arief Budiman (Jurnal Rekayasa Proses, 2010)
Biodiesel berhasil diproduksi dengan alkoholisis minyak jarak menggunakan katalisator zirkonia tersulfatasi. Proses alkoholisis dilakukan dalam suatu reaktor batch yang dilengkapi dengan pemanas, termokopel, pengaduk, termostat, dan pengambil sampel. Reaktor batch diisi dengan minyak jarak pagar, metanol dan katalisator. Reaksi selanjutnya dilakukan selama 120 menit dan sampel diambil setiap 15 menit. Model kinetika reaksi kimia disusun dan diselesaikan dengan MATLAB. Nilai faktor frekuensi tumbukan untuk reaksi tiga tahap adalah 5,13 x 103; 5,682 x 103, dan 2,534 x 103 (cm3/mgek) (cm3/g.kat/min). Sementara itu, nilai energi aktivasi reaksi berturut-turut adalah 4.176; 4.309,809 dan 6.018,623 kal/mol. Hasil simulasi menunjukkan bahwa tahap pengurangan trigliserida menjadi digliserida adalah tahap paling cepat dan tahap pengurangan monogliserida menjadi gliserol adalah tahap paling lambat.Kata kunci: minyak jarak pagar, alkoholisis, model kinetika reaksi, katalisator asam padatJatropha oil is a very potential source of biodiesel fuel that can be processed through alcoholysis. In the present work, a study on alcoholysis of Jatropha oil with the use of solid acid catalyst was conducted in a wellmixed batch reactor. The study involved varying reaction temperatures of 100°C to 140°C, ethanol-oil molar ratio of 9, agitation speed of 1000 rpm and catalyst loading of 3% with respect to the oil. The reaction was carried out for 120 minutes; meanwhile samples were taken from the reactor every 15 minutes for glycerol analysis. In order to predict kinetics parameter of the alcoholysis reaction, a mathematical model of consecutive reactions was developed. The Matlab software was used to solve the simultaneous differential equations. Over the range of variables used in the experiment, the mathematical model was able to fit the experimental data quite well. The calculation results showed that the values of collision frequency factor for the consecutive reactions are 5.13 x 103; 5.682 x 103, and 2.534 x 103 (cm3/mgek) (cm3/g.cat/min). Meanwhile, the activation energies for the consecutive reaction are 4,176; 4,310 and 6,019 cal/mol. Keywords: jatropha curcas, methanolysis, kinetics modeling, solid acid catalyst